ANALISIS FAKTOR-FAKTOR YANG DIPERTIMBANGKAN DEBITUR DALAM MENGAJUKAN PINJAMAN PADA CU STELLA MARIS DI PONTIANAK - Naiyun Untung Utama (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2022)
Cooperatives in Indonesia are an economics movement of the Indonesian people who are democratic and have a social character. Cooperatives, in addition to the form of associations in which people who are economically weak work together to improve their destiny, are also businesses engaged in the economic field. That is, in addition to being and acting as an ordinary association, cooperatives also organize economic activities. Cooperatives Actually, it is said that Indonesian cooperatives have a social character, but Indonesian cooperatives should not ignore rational economic laws. Members of the cooperative cooperate in organizing production, buying, selling, savings and loans or credit, purchasing services and so on. The types of cooperatives that exist and develop today are: savings and loan cooperatives, credit cooperatives, production cooperatives, consumption cooperatives, multipurpose cooperatives. This study aims to find out what factors are considered by debtors in applying for a loan at CU Stella Maris in Pontianak. The method used in this study is a quantitative research method with a quantitative descriptive approach. The variables in this study are location, interest rate, guarantee, and service. The population in this study was debtors who borrowed from CU stella maris in Pontianak, the number of respondents determined was 30 respondents. Sample determination using nonprobability sampling, namely by purposive sampling, meaning the determination of the sample based on certain objectives and considerations. Data collection was carried out through questionnaires and observations. Data analysis using Cochran Q Test analysis. Research results Based on the results of the Cochran Q-Test test which was carried out as many as 1 test, it can be concluded that all respondents agreed to choose the attributes of location, interest rate, guarantee and service as attributes that are considered by consumers in applying for a loan at CU Stella Maris in Pontianak. This is evidenced by testing using Cochran Qtest, where in the submission, the results of Qhitung (6.30) < Qtabel (7.81) were obtained. In accordance with the results of these calculations and the hypothesis that has been previously stated, the four attributes above are considered valid as attributes that are considered by debtors in applying for a loan at CU Stella Maris in Pontianak.